Mechanical Irritation in Vascularized Composite Tissue Allotransplantation Triggers Localized Skin Rejection. Issue 5 (May 2020) - Messner, Franka; Fischer, Anna-Christina; Runggaldier, Elias; Sprung, Susanne; Müller, Jule; Eiter, Sebastian; Gantschnigg, Antonia; Zelger, Bettina; Zelger, Bernhard; Wolfram, Dolores; Öfner, Dietmar; Hautz, Theresa; et al.
Abstract : Background: Mechanical and thermal stress has been observed to trigger skin rejection in hand-transplanted patients. This study aims to investigate this phenomenon. Methods: Syngeneic and allogeneic orthotopic hindlimb transplantations were performed using male rats (Brown Norway to Lewis). Using a specially designed device, standardized mechanical skin irritation at a force of 5 N was applied to the planta pedis of the transplanted limb for 10 days, 4 times daily for 10 minutes. Biopsies, taken on day 10 and after a 5-day observational period, were assessed for macroscopic alterations using a standardized scale, by histopathology and immunohistochemistry, and for inflammatory protein expression using Luminex technology. Results: Allogeneic animals displayed significant aggravated macroscopic skin alterations compared with naive ( P < 0.0001) and syngeneic controls ( P = 0.0023). Histopathology showed a trend toward higher rejection/inflammation grades in allogeneic animals compared with syngeneic controls. Minor skin alterations in syngeneic limbs recovered quickly; however, in allogeneic limbs, macroscopic skin alterations were significantly more pronounced ( P < 0.0001) 5 days after irritation. Interleukin-1b and interferon-γ levels were upregulated in skin of allogeneic limbs. Conclusions: Mechanical skin irritation in vascularized composite allotransplantation can trigger localized skin inflammation consistent with rejection.